Population Structure and Regeneration Status of Woody Species in Kenech Forest, Southwest Ethiopia - Sewale Balemlay; Mammo Siraj (International Journal of Forestry Research)
Understanding the structural pattern and regeneration status of tree species is an important measure taken to assess the vegetation dynamics and their destruction factors species as well as management history and ecology of the forest. This study was conducted with the objective to assess the species diversity, structure, and regeneration status of woody species in Kenech natural forest, Ethiopia. Systematic random sampling method was employed as a sampling design for the collection of vegetation data. Accordingly, 40 plots of 20 m × 20 m were laid at every 100 m along four parallel transect lines following altitudinal gradient. Any woody species of trees and shrubs with the diameter at breast height (DBH) ≥2.5 cm was measured at 1.5 m from the ground. In each sample plots, all woody species seedling, sapling, and mature woody species were counted and recorded. A total of 80 plant species categorized into 67 genera and 28 families were recorded and identified, for description and analysis of vegetation structure. Structural analysis of the Kenech natural forest revealed a density of 840 stems/ha and a total basal area of 56.8 m2/ha. About 80.36% of the individuals are found in the first two classes (2.5–10 and 10–20 cm). The general pattern of DBH class distribution of woody species in the study area revealed an inverted J shape indicating the presence of a high density of trees in the lower DBH class than in the higher. The most dominant tree species relatively with the highest importance values recorded in the area were Pouteria adolfi-friedericii, Podocarpus falcatus, Celtis africana, Mimusops kummel, Pyschotria orophila, and Olea capensis subsp. macrocarpa. Forty-two species (64.61%) were represented by both seedling and sapling class, whereas 9 species (13.84%) were not regenerating.